Improving biosensing activity to carcinoembryonic antigen with orientated single domain antibodies. Issue 12 (December 2017) - Liu, Jinny L.; Raghu, Deepa; Anderson, George P.; Goldman, Ellen R.; Christodoulides, Joseph A.; Raphael, Marc P.
Abstract: Carcinoembryonic antigen (CEA), also referred as CEACAM5, is integral to the adhesion process during cancer invasion and metastasis and is one of the most widely used tumor markers for assisting the diagnosis of cancer recurrence and cancer metastasis. Antibodies against CEA molecules have been developed for detection and diagnostic applications following tumor removal. Single domain antibodies (sdAbs) against CEA isolated from dromedary and llama exhibited high specificity in binding to tumor cells. However, because these CEA sdAbs were not designed to be orientated when conjugated to surface sensors, there is potential for significant improvements in their activity and limit of detection. Herein we modified the CEA sdAbs with two different C-terminal fusions designed to aid with orientation by way of the tail's charge and biotin binding. A fusion which incorporated the C-terminus addition of a positively charged tail (B5-GS3K) improved biosensor sensitivity to CEA while also retaining the sub-nanomolar binding affinity and thermal stability of the unmodified sdAb. Using our fabricated surfaces on bare gold chips and a multiplexed surface plasmon resonance imager (SPRi), we quantified the specific binding activities, defined as the percentage of bound epitopes to the total immobilized, of the sdAb fusions and anti-CEA mAb. Our results demonstrate that monovalent B5-GS3K exhibited significantly improved binding activity, approximately 3-fold higher than bivalent mAb.